Terapia gênica com interferon-alfa no controle do câncer colorretal - Gorgulho, Carolina Mendonça [UNESP] (2015)
Interferon alpha (IFN-α) is a type I IFN with great therapeutic potential, since it is able to directly fight tumor cells and enhance the maturation of dendritic cells (DCs), the main antigen-presenting cells, required for an effective antitumor response. However, the systemic administration of cytokines can induce severe collateral effects. Therefore, the induction of cytokine secretion in situ should represent a more adequate approach for cytokine-based immunotherapy. Thus, the goal of this study was to induce IFN-α secretion by colon cancer cells by transduction with a lentivirus vector carrying the human IFN-α gene, followed by analysis of its immunomodulatory potential over DCs. Transduction was made with different multiplicities of infection (MOIs - 0.3, 1.0, 2.0 and 4.0) to evaluate the dose-dependent effects. Such cells were co-cultured with monocyte-derived DCs from healthy donors (DC-0.3, DC-1.0, DC-2.0 and DC-4.0). Forty-eight hours later, DCs were evaluated for their phenotype (surface activation/maturation markers) by flow cytometry, their ability to induce allogeneic response in a mixed leukocyte reaction (MLR) and effectiveness to induce cytotoxic T cells. We observed that transduction with Lego-GFP, but not Lego-IFN, increased tumor cells' immunogenicity with up-regulation of the markers CD54 and HLA-DR. Co-culture of Lego-IFN-transduced tumor cells with DCs slightly enhanced their activation phenotype but not their potential to stimulate T cell proliferation in vitro. Furthermore, we observed that lymphocytes cultured with DC-2.0 produced higher levels of IFN-γ, suggesting an induction of Th1 profile on T cells, while DC-GFP induced more IL-10 and IL-4. Additionally, DC-4.0 was more efficient in generating cytotoxic T lymphocytes (CTLs) that the control DC, however DC-GFP induced even more CD8+T cell proliferation. The enhancement of tumor cell immunogenicity and the superior induction of CLTs ...